2020
DOI: 10.1109/access.2020.3024888
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on the Reactive Electromagnetic Energies and Q factors of Antennas

Abstract: It is required to calculate the stored reactive energy of an antenna in order to evaluate its Q factor. Although it has been investigated for a long time, some issues still need further clarification. The main difficulty involved is that the reactive energy of an antenna tends to become infinitely large when integrating the conventionally defined energy density in the whole space outside a small sphere containing the antenna. The reactive energy is usually made to be bounded by subtracting an additional term a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 52 publications
(70 reference statements)
9
24
0
Order By: Relevance
“…Note that the observation surface is not required to approach infinity for evaluating the radiative power with the radiative power flux density vector. It can be checked that the result is in consistent with that obtained using the Poynting vector, as has been shown in [14] that 1 1R e 0 4 4…”
Section: Radiation Of Harmonic Sourcessupporting
confidence: 84%
See 3 more Smart Citations
“…Note that the observation surface is not required to approach infinity for evaluating the radiative power with the radiative power flux density vector. It can be checked that the result is in consistent with that obtained using the Poynting vector, as has been shown in [14] that 1 1R e 0 4 4…”
Section: Radiation Of Harmonic Sourcessupporting
confidence: 84%
“…For electromagnetic pulse sources, the surface integrals are zeros since we can always put the observation surface outside the region containing the fields. For harmonic waves, it can be proved that the surface integral at S  in (21) approaches zero, while that in (22) may be a nonzero but finite value [14].…”
Section: Radiation Of Pulse Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…For harmonic fields, the total electromagnetic energy obtained by integrating the conventional energy densities of   0.5  D E and   0.5  B H over the infinite three-dimensional volume is infinite because they account for the total energy consisting of the radiative energy and the reactive energy. For harmonic fields over the time interval ( t     ), the radiative energy occupies the whole space and is infinitely large [14]. Some researchers suggested that those fields associated with the propagating waves should not contribute to the stored reactive energies.…”
Section: Introductionmentioning
confidence: 99%